Hole spin injection from a GaMnAs layer into GaAs-AlAs-InGaAs resonant tunneling diodes - Rodrigues, D.H.; Brasil, M.J.S.P.; Orlita, M.; Kunc, J.; Galeti, H.V.A.; Henini, M.; Taylor, D.; H.V.A., Y.G. (IOP Publishing, 2016)
We have investigated the polarization-resolved electroluminescence (EL) of a p–i–n GaAs/AlAs/InGaAs resonant tunneling diode (RTD) containing a GaMnAs (x  =  5%) spin injector under high magnetic fields. We demonstrate that under hole resonant tunneling condition, the GaMnAs contact acts as an efficient spin-polarized source for holes tunneling through the device. Polarization degrees up to 80% were observed in the device around the hole resonance at 2 K under 15 T. Our results could be valuable for improving the hole-spin injection in GaMnAs-based spintronic devices.